PENDAMPINGAN GURU DALAM PEMAHAMAN KONSEP LOCAL WISDOM DAN PENYUSUNAN SOAL BERBASIS HOTS SEBAGAI UPAYA MENGEMBANGKAN BERPIKIR KREATIF SISWA SMP KOTA AMBON - Papilaya, Pamella Mercy; Smith, Alwi; Tuapattinaya, Prelly M J; Persulessy, Audriel Eluzay (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Assessment is an important component in the learning process. The type of assessment provided must be in accordance with the characteristics of the subject and learning outcomes. Teachers' understanding of science concepts and preparation of HOTS questions is needed in the process of assessing student achievement. Learning in the small islands of Maluku requires teacher strategies in understanding the concept of local wisdom and preparing HOTS-based science questions as an effort to develop students' creative thinking skills in understanding local wisdom concepts and preparing HOTS-based science questions to develop students' creative thinking skills. The training and mentoring is carried out with a classical in-service training pattern, and on the job learning. The results of the service show that the ability of teachers to analyze local wisdom materials varies and needs to be assisted because they do not understand developing HOTS questions, and are used as guidelines for the success of the learning process for local wisdom materials